2015
DOI: 10.1038/mp.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bipolar disorder patient-specific induced pluripotent stem cells from a family reveals neurodevelopmental and mRNA expression abnormalities

Abstract: Bipolar disorder (BD) is a common neuropsychiatric disorder characterized by chronic recurrent episodes of depression and mania. Despite evidence for high heritability of BD, little is known about its underlying pathophysiology. To develop new tools for investigating the molecular and cellular basis of BD we applied a family-based paradigm to derive and characterize a set of 12 induced pluripotent stem cell (iPSC) lines from a quartet consisting of two BD-affected brothers and their two unaffected parents. Ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
142
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 73 publications
6
142
1
1
Order By: Relevance
“…We observed no differences in neuronal induction efficiency and yield among LiR, LiNR, or unaffected patient-derived hiPSCs, all of which showed similar expression of neuronal markers [Tau, βIII-tubulin (Tuj1), MAP2, vGLUT, GABA] and produced neural progenitor cells (NPCs) and electrophysiologically active (17) glutamatergic (vGLUT + ) and GABAergic (GABA + ) neurons that initially expressed markers consistent with a dorsal anterior forebrain cortical phenotype (SI Appendix, Figs. S2 E-L and S3 A-J) (17)(18)(19)(20). For our in vitro studies, we elected to preserve the distinction made by clinicians between LiR and LiNR patients (5)(6)(7)(8) and to probe lithium's protein targets within LiR BPD neurons (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed no differences in neuronal induction efficiency and yield among LiR, LiNR, or unaffected patient-derived hiPSCs, all of which showed similar expression of neuronal markers [Tau, βIII-tubulin (Tuj1), MAP2, vGLUT, GABA] and produced neural progenitor cells (NPCs) and electrophysiologically active (17) glutamatergic (vGLUT + ) and GABAergic (GABA + ) neurons that initially expressed markers consistent with a dorsal anterior forebrain cortical phenotype (SI Appendix, Figs. S2 E-L and S3 A-J) (17)(18)(19)(20). For our in vitro studies, we elected to preserve the distinction made by clinicians between LiR and LiNR patients (5)(6)(7)(8) and to probe lithium's protein targets within LiR BPD neurons (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 99%
“…S1) were reprogrammed to hiPSCs via nonintegrating episomalmediated (42), lentivirus-mediated (1), or retrovirus-mediated (19) gene transfer, characterized (43), and differentiated to NPCs and cortical interneurons, as per our routine and as previously described (17)(18)(19)(20). Protein isolation, 2D-DIGE and SILAC, Western blotting, and coimmunoprecipitation were performed as described previously (17,28).…”
Section: Methodsmentioning
confidence: 99%
“…Recent findings with bipolar disorder patient iPSC-derived neural progenitor and neuronal cell models provide growing support for this notion. This includes studies by Madison et al 55 employing multiplexed mRNA expression assays and high-content imaging to phenotype iPSC-derived neural progenitors and neurons from bipolar disorder subjects relative to controls. Following a family based design, and a strategy designed to isolate a specific subpopulation of CXCR4-positive neural progenitor cells by multi-chromatic, fluorescence-activated cell sorting, the authors observed differential expression of key for neurodevelopmental genes in progenitor cells from the two bipolar disorder subjects not present in their unaffected parents 55 .…”
Section: Phenotypic Assays In Human Ipsc Models Of Neuropsychiatrimentioning
confidence: 99%
“…This includes studies by Madison et al 55 employing multiplexed mRNA expression assays and high-content imaging to phenotype iPSC-derived neural progenitors and neurons from bipolar disorder subjects relative to controls. Following a family based design, and a strategy designed to isolate a specific subpopulation of CXCR4-positive neural progenitor cells by multi-chromatic, fluorescence-activated cell sorting, the authors observed differential expression of key for neurodevelopmental genes in progenitor cells from the two bipolar disorder subjects not present in their unaffected parents 55 . Consistent with these expression differences, deficits in neurogenesis were also observed in the two bipolar disorder subjects compared to their unaffected parents using imaging and neural lineage-specific markers as functional read outs 55 .…”
Section: Phenotypic Assays In Human Ipsc Models Of Neuropsychiatrimentioning
confidence: 99%
See 1 more Smart Citation